Las Varas : Ritual and Ethnicity in the Ancient Andes - Tsai, Howard, 1979- (Book collections on Project MUSE., 2020)
"Archaeological data from Las Varas, Peru, that establish the importance of ritual in constructing ethnic boundaries"--